Performance studies with antihistamines. - Clarke, C H (1978)
1 Effect of four antihistamines, chlorpheniramine (4 mg), clemastine (1 mg), promethazine (10 mg) and terfenadine (60 mg), on visuo-motor coordination and on subjective assessments of performance and well-being were compared with placebo in six healthy females from 0.5--7.0 h after morning ingestion of each drug. The study was double-blind, and the doses used were believed to be equally potent in their antihistaminic activity. 2 There was impaired performance 1.5 h (P less than 0.01) after chlorpheniramine, 3.0 h (P less than 0.05) and 5.0 h (P less than 0.01) after clemastine, and 3.0 h (P less than 0.01) and 5.0 h (P less than 0.001) after promethazine. It was not possible to establish effects on performance after ingestion of terfenadine. Subjective assessments of performance were not altered. 3 The subjects as a group reported improved alertness (P less than 0.05) and improved wakefulness (P less than 0.05) 0.5 h and 3.5 h respectively after ingestion of terfenadine, and were less energetic (P less than 0.05) 7.0 h after ingestion of chlorpheniramine. There were not other consistent changes in assessments of well-being.